2021
DOI: 10.3390/ijerph18052331
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Skills in Youth Basketball Players: Diagnostic and External Validation of a Video-Based Assessment

Abstract: Decision-making is a central skill of basketball players intending to excel individually and contribute to their teams’ success. The assessment of such skills is particularly challenging in complex team sports. To address this challenge, this study aimed to conceptualize a reliable and valid video-based decision-making assessment in youth basketball. The study sample comprised youth basketball players of the German U16 national team (n = 17; MAge = 16.01 ± 0.25 years) and students of a sports class (n = 17; MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…In accordance with the present results, previous studies have demonstrated that weekly open skills training had no significant impact on children's inhibitory control and working memory (Ishihara et al, 2018), while prolonged training of the same type five times a week improved their cognitive flexibility, inhibitory control, and working memory (Hillman et al, 2014). Basketball is a cognitively engaging exercise that requires the understanding of rules, peer competition, and the memory of technical movements, all of which require the participation of EFs (Rösch et al, 2021). It can be concluded that increasing the frequency of a cognitively engaging exercise has a positive effect on children's EFs.…”
Section: Switching Tasksupporting
confidence: 91%
“…In accordance with the present results, previous studies have demonstrated that weekly open skills training had no significant impact on children's inhibitory control and working memory (Ishihara et al, 2018), while prolonged training of the same type five times a week improved their cognitive flexibility, inhibitory control, and working memory (Hillman et al, 2014). Basketball is a cognitively engaging exercise that requires the understanding of rules, peer competition, and the memory of technical movements, all of which require the participation of EFs (Rösch et al, 2021). It can be concluded that increasing the frequency of a cognitively engaging exercise has a positive effect on children's EFs.…”
Section: Switching Tasksupporting
confidence: 91%
“…LSTM can effectively solve this problem by capturing the dependencies of long time series more easily than RNN. However, it has been experimentally observed that in some cases, especially in very long sequences, the LSTM does not always remember long interdependencies and correlations correctly [13]. is leads to a decrease in the performance of the neural network with the passage of time, which leads to the so-called longrange dependence problem.…”
Section: Attention Mechanismsmentioning
confidence: 99%
“…CNN is an artificial neural network that has dominated in various computer vision tasks [13,22,23]. e key feature of the convolution operation is weight sharing: the kernel is shared over all image locations.…”
Section: Cnnmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the above-mentioned evidence strongly suggests that cognitive abilities are crucial in team sports such as basketball, the evidence concerning expertise-related differences (e.g., amateur athlete vs. elite athlete) is not exhaustive, as most of the available studies compared basketball athletes to non-athletes [ 13 , 14 ]. Thus, further research is necessary to reach a more comprehensive and nuanced understanding of the effect of the sport-specific expertise level on cognitive performance [ 1 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%